Multiple post-transcriptional regulatory mechanisms in ferritin gene expression. - Mattia, E (1989)
We have investigated the mechanisms involved in the regulation of ferritin biosynthesis in K562 human erythroleukemia cells during prolonged exposure to iron. We show that, upon addition of hemin (an efficient iron donor) to the cell culture, the rate of ferritin biosynthesis reaches a maximum after a few hours and then decreases. During a 24-hr incubation with the iron donor the concentrations of total ferritin heavy (H) and light (L) subunit mRNAs rise 2- to 5-fold and 2- to 3-fold, respectively, over the control values, while the amount of the protein increases 10- to 30-fold. The hemin-induced increment in ferritin subunit mRNA is not prevented by deferoxamine, suggesting that it is not directly mediated by chelatable iron. In vitro nuclear transcription analyses performed on nuclei isolated from control cells and cells grown in the presence of hemin indicate that the rates of synthesis of H- and L-subunit mRNAs remain constant. We conclude that iron-induced ferritin biosynthesis is governed by multiple post-transcriptional regulatory mechanisms. We propose that exposure of cells to iron leads to stabilization of ferritin mRNAs, in addition to activation and translation of stored H- and L-subunit mRNAs.